Tridimensional Leadership Maturity: Analyzing Spiritual, Emotional, And Moral Dimensions of Female Principals in Indonesia's Transform School Program - Kartiwi, Asti Putri; Banu, Shamsiah; Sary, Fetty Poerwita; Sutopo, Timbul Wahyu (Universitas Ahmad Dahlan, 2025)
Background. Despite female teachers comprising the global teaching workforce majority, significant gender disparities persist in educational leadership positions, necessitating holistic approaches integrating spiritual, emotional, and moral intelligence for effective educational transformation. This study aims to analyze tridimensional spiritual leadership implementation by female principals at SDN 72 and SDN 76 Central Bengkulu District within Indonesia's